Differences between practice patterns of conventional and naturopathic GPs in Germany - Laux, Gunter; Musselmann, Berthold; Kiel, Marion; Szecsenyi, Joachim; Joos, Stefanie (PLOS ONE, 2016)
Background Limited evidence exists whether practice patterns of general practitioners (GPs) who have additionally completed training in naturopathy are different from those of conventional GPs. We aimed to assess and compare practice patterns of GPs in conventional and naturopathic GPs. Methods Routine data from 41 GPs (31 with and 11 without additional qualification in NP, respectively) and 180,789 patients, drawn from the CONTinuous morbidity registration Epidemiologic NeTwork (CONTENT)-registry and collected between 2009 and 2014, were used. To assess practice patterns determinants of (non-)phytopharmaceutical prescriptions, referrals and hospitalizations were analyzed using mixed-effects Poisson regression models. As explanatory variables, the qualification of the GP in NM, the age group and sex of the patient, as well as bivariate interactions between these variables were considered. Results GPs additionally qualified in naturopathy exhibited higher rates of phytopharmaceutical prescriptions (p<0.034; independent effect) compared to conventional GPs. This association was not observed with respect to non-phytopharmaceutical prescriptions. However, interaction effects between qualification and age group as well as sex were present with respect to both phytopharmaceutical and non-phytopharmaceutical prescriptions (all p<0.001). No further independent association existed between qualification and either referral rates or hospitalization rates, but again interactions between qualification and age group and sex (only referrals) were statistically significant (all p<0.0001). Conclusion The results show that the rate of phyto-pharmaceutical prescriptions are generally higher when the GP has an additional qualification in naturopathy. Further differences in practice patterns between conventional and naturopathy GPs could be subject to certain age groups and sex. However, the magnitude of these differences seem to be rather small.